Meningkatkan Solidaritas Anak Melalui Kegiatan Pendampingan Sekami Di Stasi Santa Theresia Loang - Theresia Nuli; Maria Gelu Tolok; Anggela Marice Ema Duan; Skolastika Lelu (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Community Service Activities were carried out at Santa Theresia Loang Station. This activity was carried out because nowadays in their daily lives, children are less likely to share with friends who need help, prefer playing online games to interacting with others, are not involved in spiritual activities, like to use bad words, like to fight with friends. As a result, the ability to show solidarity by working together, sharing, and caring for others is reduced. The purpose of this activity is to increase children's solidarity through our mentoring activities. This activity was attended by 20 children from our group who are active at the Loang station. The mentoring method used in this activity is participatory mentoring by being directly involved with the children from our group. This Community Service Activity was carried out for 3 months, namely from August to October 2025. This activity was carried out every Saturday afternoon at 16.00 and Sunday after the Eucharist celebration. The result of this activity is that after participating in the Sekami mentoring activities, the children of Sekami Stasi Santa Theresia Loang are increasingly aware of the importance of a sense of brotherhood, togetherness, sharing, and supporting each other both between groups and between individuals, both through words.